Vannevar Bush papers - Bush, Vannevar, 1890-1974.
Correspondence, memoranda, writings, reports, speeches, minutes, laboratory and other notes, articles, book file, scientific papers, diagrams, patents, clippings, press releases, printed matter, financial papers, biographical data, family papers, photographs, and other papers relating primarily to Bush's role in coordinating the scientific community for defense efforts during and after World War II as chairman of the National Defense Research Committee and director of its successor, the Office of Scientific Research and Development, where he supervised the Manhattan Project and other programs. Other agencies represented include the National Advisory Committee for Aeronautics, Joint Commission on New Weapons of the Joint Chiefs of Staff, National Science Foundation, National Research Council, and National Academy of Sciences.
Bush's corporate and academic affiliations are documented by files on American Telephone and Telegraph Company, Merck & Co., Johns Hopkins University, Massachusetts Institute of Technology, and Tufts University. Also represented are the Brookings Institution, Carnegie Institution of Washington, Franklin Institute, Metals & Controls Corporation, Smithsonian Institution, and U.S. Patent Office. Also documented are Bush's views on the interrelationship between science and government, technological influences on postwar U.S.-Soviet relations, international control of nuclear energy, and the loyalty controversies during the McCarthy era. Includes material pertaining to Bush's interest in air-engines, fly rods, immunological reactions, medicine, optics, ornithology, solar pumps, and zoology.
Correspondents include Dean Acheson, Henry Harley Arnold, Omar Nelson Bradley, Niels Henrik David Bohr, Robert A. Choate, K.T. Compton, James Bryant Conant, Bradley Dewey, Charles Dollard, Dwight D. Eisenhower, James Forrestal, W.W. Garth, Caryl Parker Haskins, D.C. Josephs, James Rhyne Killian, R.C. Leffingwell, David Eli Lilienthal, F. Alexander Magoan, Robert Porter Patterson, Don Krasher Price, Redfield Proctor, Palmer Cosslett Putnam, Alfred N. Richards, Elihu Root, Oscar M. Ruebhausen, John T. Rule, Orville J. Schell, Leslie Earl Simon, Carl Spaatz, W.H. Timble, Harry S. Truman, Tracy S. Voorhees, Warren Weaver, Bethuel Matthew Webster, Carroll L. Wilson, and Robert E. Wilson.
Physicist, engineer, government official, and science administrator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Acheson, Dean, -- 1893-1971 -- Correspondence; Arnold, Henry Harley, -- 1886-1950 -- Correspondence; Bradley, Omar Nelson, -- 1893-1981 -- Correspondence; Bohr, Niels, -- 1885-1962 -- Correspondence; Choate, Robert A., -- 1912- -- Correspondence; Compton, K. T. -- 1887-1954 -- Correspondence; Conant, James Bryant, -- 1893-1978 -- Correspondence; Dewey, Bradley, -- 1887-1974 -- Correspondence; Dollard, Charles, -- 1907-1977 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Forrestal, James, -- 1892-1949 -- Correspondence; Garth, W. W. -- Correspondence; Haskins, Caryl P. -- 1908-2001 -- Correspondence; Josephs, D. C. -- 1893-1977 -- Correspondence; Killian, James Rhyne, -- 1904- -- Correspondence; Leffingwell, R. C. -- 1878-1960 -- Correspondence; Lilienthal, David Eli, -- 1899-1981 -- Correspondence; Magoan, F. Alexander -- Correspondence; McCarthy, Joseph, -- 1908-1957.; Patterson, Robert Porter, -- 1891-1952 -- Correspondence; Price, Don Krasher -- Correspondence; Proctor, Redfield, -- 1831-1908 -- Correspondence; Putnam, Palmer Cosslett, -- 1900- -- Correspondence; Richards, Alfred N. -- 1876-1966 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Ruebhausen, Oscar M. -- Correspondence; Rule, John T. -- Correspondence; Schell, Orville J. -- Correspondence; Simon, Leslie Earl, -- 1900- -- Correspondence; Spaatz, Carl, -- 1891-1974 -- Correspondence; Timble, W. H. -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Voorhees, Tracy S. -- 1890-1974 -- Correspondence; Weaver, Warren, -- 1894-1978 -- Correspondence; Webster, Bethuel M. -- 1900-1989 -- Correspondence; Wilson, Carroll L. -- Correspondence; Wilson, Robert E. -- 1893-1964 -- Correspondence; American Telephone and Telegraph Company; Brookings Institution; Carnegie Institution of Washington; Franklin Institute (Philadelphia, Pa.); Johns Hopkins University; Manhattan Project (U.S.); Massachusetts Institute of Technology; Merck & Co; Metals & Controls Corporation; National Academy of Sciences (U.S.); National Research Council (U.S.); National Science Foundation (U.S.); Smithsonian Institution; Tufts University; United States. -- Council of National Defense. -- National Defense Research Committee; United States. -- Joint Chiefs of Staff. -- Joint Commission on New Weapons and Equipment; United States. -- National Advisory Committee for Aeronautics; United States. -- Office of Scientific Research and Development; United States. -- Patent Office; Air-engines.; Cold War -- Technology; Fishing rods; Immunology